Different Moods Lead to Different Creativity: Mediating Roles of Ambiguity Tolerance and Team Identification. Issue 2 (2nd April 2020) - Hwang, Tae Jin; Choi, Jin Nam
ABSTRACT: The present study examined the effects of workplace mood states on employee creativity. Workplace mood was classified into four categories based on valence and activation to address a recent debate regarding the ambivalent effects of positive and negative moods on creativity and to examine the significance of the activation level of a given mood. To clarify the mood–creativity relationship, the four kinds of moods were proposed to have distinct effects on proactive and responsive engagement in creativity. The research hypotheses were tested using the data collected from 292 employees and 109 managers of Korean organizations. Multilevel path-analytic model indicated that positive and negative activating moods were positively related to proactive and responsive creativity, respectively. The effect of positive activating mood was mediated by ambiguity tolerance and team identification. Positive deactivating mood was negatively related to both types of creativity, whereas negative deactivating mood was unrelated to either type.